The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1159/000127166
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Demonstration of the Mineralocorticoid Receptor in Ocular Tissues

Abstract: We studied the presence of the mineralocorticoid receptor (MCR) in the eye with the aid of a number of immunochemical techniques. Immunoblotting with a polyclonal antibody, directed against the rat renal MCR, revealed a single band of about 102 kD in extracts prepared from whole bovine or rat retina similar to that observed in cytosol from the kidney and myocardium from these species. Isolated cells of the bovine retinal pigment epithelium (RPE) similarly exhibited a 98- to 102-kD band in Western blots develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 27 publications
5
39
0
Order By: Relevance
“…Figure 1 show that the cytosol from the proerythroblastic TF1 (a) and the HEL (c) cell lines were resolved as a single band of about 102 kDa in Western blots developed with the aid of the polyclonal antibody directed against the entire mineralocorticoid receptor (MCR), but the myeloblastic cell line (U937) did not exhibit this protein at all (b). This is comparable to the molecular weight in a number of other organs that are known to contain the MCR, [22][23][24][25][26] and correlates well with the theoretical molecular mass of 107 kDa calculated from the cloned product.…”
Section: Chemicals and Reagentssupporting
confidence: 79%
See 2 more Smart Citations
“…Figure 1 show that the cytosol from the proerythroblastic TF1 (a) and the HEL (c) cell lines were resolved as a single band of about 102 kDa in Western blots developed with the aid of the polyclonal antibody directed against the entire mineralocorticoid receptor (MCR), but the myeloblastic cell line (U937) did not exhibit this protein at all (b). This is comparable to the molecular weight in a number of other organs that are known to contain the MCR, [22][23][24][25][26] and correlates well with the theoretical molecular mass of 107 kDa calculated from the cloned product.…”
Section: Chemicals and Reagentssupporting
confidence: 79%
“…The MCR in the HEL cells was readily recognized by an antibody directed against the rat kidney protein purified in the presence of RU 26752 that binds specifically to this receptor. 4,22 The estimated molecular size of about 102 kDa in Western blots is compatible with the MCR in a number of peripheral organs, [22][23][24][25][26] and with the theoretical mass of 107 kDa deduced from the cloned sequence.…”
Section: Leukemiasupporting
confidence: 58%
See 1 more Smart Citation
“…Immunohistochemical localization of the mineralocorticoid receptor (Mirshahi et al, 1996(Mirshahi et al, , 1997Stokes et al, 2000;Suzuki et al, 2001) and the glucocorticoid receptor (Stokes et al, 2000;Suzuki et al, 2001) was demonstrated in NPE cells. Corticosteroid Fluorescence observation by confocal laser microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The NPE cells that face the posterior chamber are involved in the active secretion of aqueous humor (Usukura et al, 1988) and have tight junctions that act as a blood-aqueous barrier (Hirsch et al, 1977;Raviola, 1974Raviola, , 1977. In addition, the NPE cells have various steroid hormone receptors (Mirshahi et al, 1996(Mirshahi et al, , 1997Stokes et al, 2000;Suzuki et al, 2001) and are considered to modulate the aqueous humor in the maintenance of ocular homeostasis.…”
mentioning
confidence: 99%